2023
DOI: 10.1177/23294884221148615
|View full text |Cite
|
Sign up to set email alerts
|

Notes From the Editors: Spotlight on Social Media

Abstract: This issue of the International Journal of Business Communication brings a new feature to the journal-spotlight issues. Spotlight issues present articles on topics of interest among business communication researchers (based on the number of submissions the journal has received) and stuck a chord with the wider academic community (based on the number of citations these articles have received after online publication). Spotlight issues differ from our special issues in that they emerge from articles accepted by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…In addition, this article enriches the ongoing IJBC conversation about targeting communication behaviors which cultivate DEI success (Austin & Bisel, 2022; Gans & Monica Zhan, 2023; M. Mayfield & Mayfield, 2023b; Mishra et al, 2014; Yue et al, 2021). Haas and De Rozario (2020) also amplify the definition of CSR communication through extending its scope to DEI narratives “where diversity managers have the power to change values and beliefs of employees regarding diversity in the workplace by encoding new beliefs and values into social scripts that can be enacted in daily activities.…”
Section: Overview Of Csr Articlesmentioning
confidence: 96%
“…In addition, this article enriches the ongoing IJBC conversation about targeting communication behaviors which cultivate DEI success (Austin & Bisel, 2022; Gans & Monica Zhan, 2023; M. Mayfield & Mayfield, 2023b; Mishra et al, 2014; Yue et al, 2021). Haas and De Rozario (2020) also amplify the definition of CSR communication through extending its scope to DEI narratives “where diversity managers have the power to change values and beliefs of employees regarding diversity in the workplace by encoding new beliefs and values into social scripts that can be enacted in daily activities.…”
Section: Overview Of Csr Articlesmentioning
confidence: 96%
“…The ability to facilitate connectivity between users through links to websites, information sources, and other users allows the majority of social media platforms to flourish. Mayfield (2008) stated that "Most kinds of social media drive on their connectedness, making use of links to other sites, resources, and people." The fact that users can connect with other users, access websites, resources, and other users easily when looking for information is the reason why most types of social media are expanding quickly.…”
Section: Fan-page Engagementmentioning
confidence: 99%
“…This increasing diversity not only challenges firms and users in their adoption (Yee et al , 2021) but also provides scholars with a need to theoretically grasp and conceptualize these technologies. Management scholars have examined smaller ranges of technologies for focused processes, such as knowledge sharing (Razmerita et al , 2014), self-presentation and identity creation (Kaplan and Haenlein, 2010) or online conversations more generally (Mayfield, 2008). In other disciplines, such as communication studies, scholars have identified specific affordances, such as the visibility, editability, interactivity or connectivity of (social) media technologies (Ariel and Avidar, 2015; Treem and Leonardi, 2013).…”
Section: Introductionmentioning
confidence: 99%